Stress, Anger and Coping among Dental Students (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background : Medical course and dentistry have always been considered to be stressful to the studentsbecause of its depth, diversity and competitiveness. These are very extensive course spread 4 to 5 years inIndia. Stress sometimes can lead to anger, which cause even more stress. Prolonged stress and anger cantake a toll on the students, both physically and emotionally. It is important to eliminate them by attemptingcontrol management and implication of positive coping strategiesAim : This study aims to investigate level and source of stress, anger, anxiety, depression and associatedcoping mechanisms among dental studentsMaterial and method : A link to an online questionnaires conducted through Surveymonkey was distributedamong all third-year, fourth-year and final-year students.Result : The first major stressor for the dental students was clinical requirements (61.3%) followed bypatient’s behavior, peer pressure/competitiveness, education program and language barrier. Taking sometime off to rest (20.3%), talking to a friend (%23.9) and listening to music (19%) were the most commonlyreported coping mechanisms (Table 3).Conclusion : The primary sources of stress as perceived by the dental students were peer pressure/competitiveness, patient’s behavior and clinical requirements. In the present study, female dental studentsreported higher stress levels and a wider range of coping than male students, hence a stress managementprogram should be implemented that focusing towards dental students. The preventive and interventionmust be sought and directed as this need early in the student years.